Pengaruh Sanksi Pajak, Kesadaran Wajib Pajak Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi Yang Terdaftar Pada Kantor Pelayanan Pajak (KPP) Pratama Semarang Barat. - Suyanti Suyanti; Putu Sulastri (JURNAL RISET MANAJEMEN (JURMA), 2023)
The aim of the research is to analyze the influence of Tax Sanctions, Taxpayer Awareness, and Fiscal Services on Individual Taxpayer Compliance Registered at the West Semarang Primary Tax Service Office (KPP). The population of individual taxpayers registered at the West Semarang Tax Service Office (KPP) is 12,736 people. The sample/respondent was taken as many as 100 respondents with the Slovin formula, and was determined using the accidental sampling technique. The results showed that tax sanctions had a positive effect (β 1 = 0.338) and t count = 4.326 > t table = 1.658 with a significance value = 0.000 <; a = 0.05. Thus, the hypothesis 1). (H1) that tax sanctions have a positive effect on the performance of taxpayer compliance received. Taxpayer awareness has a positive effect (β 2 = 0.262) and t count = 4.189 > t table = 1.658 with a significance value = 0.000 <; a = 0.05. Thus, hypothesis 2). (H2) that taxpayer awareness has a positive effect on accepted taxpayer compliance. Fiscal services have a positive effect (β 3 = 0.433) and t count = 7.507 > t table = 1.658 with a significance value = 0.000 <; a = 0.05. Thus, hypothesis 3). (H3) that tax authorities have a positive effect on tax payer compliance.